(untitled) (Jurnal Teknologi (Sciences & Engineering), 2018)
The use of Carbon Nanotubes (CNTs) as a reinforcement in conductive polymer composite (CPCs) of bipolar plates nowadays attracts a great deal of attention. Therefore, the aim of this study was to identify the most effective and suitable ratio of CNTs loading in multi filler Graphite (G), Carbon Black (CB) composite using a medium crystallinity and low crystallinity Polypropylene (PP) denoted as MC-PP and LC-PP respectively. The composite were developed through compression molding technique with dry mixing method by using a ball mill to investigate the influence of crystallinity on the dispersion of CNTs in PP matrix. Incorporating CNTs as a third filler in G/CB/CNTs/PP nanocomposites produces a synergistic effect that enhances the electrical conductivity, flexural strength, bulk density and hardness of the nanocomposite which exceeded U.S. DOE requirement. The results indicated that CNTs was given more affect in MC-PP than LC-PP due to better electrical conductivity and mechanical properties of G/CB/CNTs/PP composite as bipolar plate.